Acitretin for the Treatment of Psoriasis: A Case Report of Long-Lasting Alopecia. Issue 1 (December 2015) - Waldman, Alexandra; Khattri, Saakshi; Rose, Sharon; Lebwohl, Mark; Kellen, Roselyn
Acitretin has been associated with alopecia and hair shaft abnormalities such as hair kinking, hair curling, poliosis, and re-pigmentation of hair color. In the majority of patients, these side effects are dose-dependent, mild, and only temporary, with hair growth reoccurring after cessation of treatment. A 65-year-old male developed severe hair loss over his entire body seven weeks into treatment. He presented to us more than six months after discontinuation of acitretin without evidence of substantial hair regrowth. Here we report one of the rare cases of long-lasting alopecia after therapy with acitretin that we believe to be a case of generalized telogen effluvium.